PENELANTARAN RUMAH TANGGA ( Kajian Hukum dan Gender ) - Nurbaity Prastyananda (Muwazah, 2016)
This paper examines the neglect of household in the perspective of law and gender. The argument, which was developed in this study is that neglect of household as one form of domestic violence, which legally regulated clearly and firmly in the Law of the Republic of Indonesia Number 23 of 2004 on the Elimination of Domestic Violence. Sociologically, neglect of household, related to the construction of gender in the context of patriarchal society, which results in gender inequality with the victims were women and children.Paper ini mengkaji tentang penelantaran rumah tangga dalam perspektif hukum dan gender. Argumentasi yang dibangun dalam kajian ini adalah, penelantaran rumah tangga sebagaisalah satu bentuk Kekerasan Dalam Rumah Tangga, yang secara yuridis diatur secara jelas dan tegas dalam Undang-undang Republik Indonesia Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan Dalam Rumah Tangga. Secara sosiologis, penelantaran rumah tangga, juga tidak lepas dari konstruksi gender yang dibangun oleh masyarakat patriarkhis, yang mengakibatkan ketimpangan gender dengan korbannya adalah perempuan dan anak.